2004
DOI: 10.1186/1471-2407-4-41
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid cystic carcinoma of the parotid metastasizing to liver: case report

Abstract: Background: Adenoid cystic carcinoma is a rare malignant parotid tumor. Metastasis can occur even a decade or more after initial treatment of the primary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 17 publications
0
31
0
3
Order By: Relevance
“…Harish et al reported a case of liver metastasis 3 years after primary parotid surgery without lung and bone involvement. The patient refused chemotherapy and died 21 months later with no evidence of local recurrence or pulmonary metastasis 4. In two separate studies liver metastasis from ACC of Bartholin gland14 and lacrimal gland15 was reported without lung and bone metastases.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Harish et al reported a case of liver metastasis 3 years after primary parotid surgery without lung and bone involvement. The patient refused chemotherapy and died 21 months later with no evidence of local recurrence or pulmonary metastasis 4. In two separate studies liver metastasis from ACC of Bartholin gland14 and lacrimal gland15 was reported without lung and bone metastases.…”
Section: Discussionmentioning
confidence: 91%
“…The distant organs involved in decreasing order of frequency are lung, bone, brain and liver. Other rare metastatic sites include stomach, choroids, kidney and skin 4. Spiro et al from the Memorial Sloan-Kettering Cancer Centre reported results of evaluation of 434 malignant minor salivary gland tumours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were able to find in literature five clinical report of liver metastases from cancer of the salivary glands (four ACC and one Mucoepidermoid Carcinoma) and three cytopathology diagnosis case-report of liver DM from ACC [16,[27][28][29][30][31][32][33] (See Table 1). Zeidan [34] instead, reports an extended right hemihepatectomy for isolated DM from ACC of the lacrimal gland 20 years after resection of the primary tumor.…”
Section: Resultsmentioning
confidence: 99%
“…It usually presents as an asymptomatic slowly enlarged mass with a characteristic propensity for perineural invasion. The natural history is often indolent and prolonged, but its course is progressive with frequent local recurrence and distant metastases, eventually with a 10-year survival reported to be less than 50% [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%